The effect of intrathecal morphine on pain following video assisted thoracoscopic surgery (VATS) (retrospective study) [Video yardimli torakoskopi (VATS) ameliyatlarinda i̇ntratekal morfinin Analjezik Etkinliǧi - Retrospektif çalişma] - (:unkn) unknown (My University, 2007)
In this retrospective study, we aimed to investigate the efficiency of intratechal morphine of 0.6 mg in patients undergoing video assisted thoracic surgery in our institutions between January 2005 and October 2007. The patients were divided into two groups as Group D (n=30) and Group M (n=33). While Group D patients received only intravenous PCA meperidine, the patients in Group M were given intratechal morphine and intravenous PCA meperidine. All patients were supplied with iv PCA pump set to deliver meperidine bolus dose10 mg and lock-out time 30 min for 48 hour. In Group M, 0.6 mg morphine in 3 ml NaCl was applied intratechally after induction of anesthesia. Pain scores, determined by visual analogue scale (VAS), were determined by evaluating observation forms and pain inquiry forms filled by nurses, recorded after extubation, at the 2nd, 8th, 12th, 24th, and 48th hours postoperatively. In Group M, VAS scores were found to be significantly lower at all measured times when compared to Group D (p<0,001). Additionally, in Group D, meperidine consumption on 1st and 2nd days were significantly higher than Group M (p<0.001 vs p<0.001, respectively), In Group M, 10 of 33 patients did not need meperidine on the 1st postoperative day. No significant side effects requiring intervention was noted. Thus it can be concluded that, intratechal morphine can provide better analgesia than iv PCA meperidine alone with less need of postoperative meperidine application and without the occurrence of significant side effects.
Keywords: Intrathecal morphine; Meperidine; Thoracoscopy